Exploring the Optimal Chemotherapy Strategy for Locoregionally Advanced Children and Adolescent Nasopharyngeal Carcinoma Based on Pretreatment Epstein-Barr Virus DNA Level in the Era of Intensity Modulated Radiotherapy - Zeng, Ziyi; Chen, Chen; Guo, Lanlan; Zhang, Cheng; Chen, Lei; Yuan, Chuanping; Lu, Lixia (Frontiers in Oncology, 2021)
Background: The purpose of this study is to explore the optimal chemotherapy strategy for locoregionally advanced children and adolescent nasopharyngeal carcinoma (LcaNPC) basing on the level of pretreatment Epstein-Barr virus DNA (pEBV-DNA) in the era of intensity modulated radiation therapy (IMRT). Methods: This real-world, retrospective study consecutively reviewed locoregionally advanced nasopharyngeal carcinoma patients younger than 22 years old from 2006 to 2016 in Sun Yat-sen university cancer center. Kaplan-Meier method with log-rank test and Cox regression model were used to investigate the survival outcomes of different chemotherapy intensity and pEBV-DNA. Treatment-related toxicity was also evaluated by a chi-square test (or Fisher exact test). Results: A total of 179 patients were enrolled, including 86 patients in high risk group (pEBV-DNA≥7,500 copies/mL) and 93 patients in low risk group (pEBV-DNA < 7,500 copies/mL). In total patients, patients with low intensity induction chemotherapy (IC courses=2) had better 5-year OS than no IC (P=0.025) and high intensity IC (IC courses>2) (P=0.044). In high risk group, low intensity IC showed significant 5-year OS (P=0.032), PFS (P=0.027), and 5-year DMFS (P=0.008) benefit than no IC. Multivariate analyses identified that no IC was a risk factor over low intensity IC for OS (HR=10.933, P=0.038) in total patients. Moreover, in high risk patients, no IC was a risk factor for 5-year OS (HR=10.878, P=0.038), 5-year PFS (HR=5.705, P=0.041) and 5-year DMFS (HR=10.290, P=0.040) compared to low intensity IC. There found no difference in survival for patients treated with or without concurrent chemotherapy. Conclusion: The two courses of platinum-based IC may be the optimal induction chemotherapy intensity to reduce risk of death, progression and distant metastasis in patients with high pEBV-DNA level.